How can we prepare music students for early career challenges?. Issue 2 (5th July 2022) - Latukefu, Lotte; Pollard, Jessica
Abstract: Earning a living via multiple income streams through a portfolio career is the reality for most music graduates. In the last 10–15 years, music conservatoires around the world have begun to recognise and respond to this reality in the way they train and prepare students for life after study (Bennet, 2008 ; Draper & Cunio, 2014 ; Rowley et al., 2015 ; Schippers et al., 2016 ). Conservatoire curricula is prescribed and controlled to ensure that students gain the skills required to build a career as a professional musician. Reforming conservatoire curricula to incorporate portfolio career training is an ongoing concern that is made more complex by the different conceptual understandings of what training for a portfolio career means (Latukefu & Ginsborg, 2018 ). This article contributes to the literature on how students conceptualise and make decisions surrounding their transition into work after graduation. It uses narrative analysis research to investigate the value of introducing career design into the curriculum of a Bachelor of Music. It incorporates narratives by students who took part in a series of interventions designed to increase self-efficacy and explores the role of career indecision in the designing of a creative career. Career indecision in this context relates to the inability of music students to conceive of what they wish for their creative career to look like after graduation, even when a decision is necessary. The narratives reveal how different factors such as family support, cultural and religious backgrounds and prior music education impact on their confidence and perceptions surrounding their ability to design and maintain a creative career. These narratives also uncovered the interplay of career exploration, career indecision and anxiety in the career decision-making process of undergraduate music students.